HUBUNGAN BERAT BADAN LAHIR RENDAH (BBLR) DENGAN KEJADIAN NEONATAL JAUNDICE DI RSUD EMBUNG FATIMAH - Adi Arianto; Luis Yulia; Ghadhidha Fedayeena (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Neonatal jaundice is a clinical condition commonly encountered during the neonatal period and remains an important concern in neonatal health care. This condition occurs as a result of elevated bilirubin levels in the blood and may be influenced by various risk factors, one of which is low birth weight (LBW), which is generally associated with hepatic functional immaturity. In neonates with LBW, the liver’s ability to conjugate and excrete bilirubin has not yet developed optimally, thereby increasing the risk of neonatal jaundice. Methods: This study employed an analytical observational design with a cross-sectional approach using medical record data. The sample consisted of 55 neonates with jaundice selected through total sampling. Data were analyzed using univariate and bivariate analyses with the Chi-square test and Contingency Coefficient. Results: A total of 36.4% of neonates had low birth weight. Physiological jaundice was found in 54.5% of cases, while pathological jaundice occurred in 45.5%. There was a statistically significant association between low birth weight and the type of neonatal jaundice (p = 0.021), with a weak strength of association (C = 0.297). Conclusion: There is a significant relationship between low birth weight and the type of neonatal jaundice; however, the strength of the association is weak. Keywords: low birth weight; neonatal jaundice; physiological; pathological; neonate.